Uso de psicofármacos em população adulta coberta pela estratégia de saúde da família. - Elise de Assis Vieira Guimarães (2022)
Brazil is the country with the highest proportion of people with anxiety disorders in the world and the fifth in cases of depression. Therefore,characterizing the profile of use of medications used to treat of mental disorders among users of Primary Health Care (PHC) in Brazil is fundamental for the elaboration of public policies in mental health. Thus, the objective of this study is to investigate the use of psychotropic drugs among an adult population assigned to the Family Health Strategy, in the municipality of Ribeirão das Neves (MG). The research participants were selected based on a systematic probabilistic sample of people aged 20 or over residing in the municipality. The prevalence of use of psychotropic drugs (antidepressants or benzodiazepines), defined as the dependent variable, as well as associated factors, was determined using univariate (Pearson's chi-square) and multivariate (logistic regression) analyses. The study sample (n=1,100) was mostly female (52.6%), with incomplete primary education (52.0%), and with monthly family income between 1 and 2.9 minimum wages (46.3 %); a mean age of 42.6 years was identified. The use of at least one psychotropic drug was reported by 8.6% of respondents, with 2.3% using only benzodiazepines, 4.7% using only antidepressants and 1.6% using both. After the multiple adjustment, female gender (OR=3.0; 95%CI=1.7-5.3), poor/very poor self-rated health (OR=2.6; 95%CI =1.4-4.7), dependence for instrumental activities of daily living (IADL - OR=1.9; 95%CI=1.0-3.6), dependence for basic activities of daily living (BADL) and IADL (OR=3.4; 95%CI=1.7-7.1), number of chronic diseases (OR=1.3; 95%CI=1.1-1.6) and the interaction term between age and education remained independently associated with the use of psychotropic drugs. Among people with less education, the older they were, the less likely they were to use psychotropic drugs; among people with higher education, the older they were, the more likely they were to use psychotropic drugs. The high prevalence of psychotropic drug use highlights the demand, which is generally characterized by underdiagnosis and undertreatment of psychiatric disorders. The multiple associated factors make it possible to outline local policies for adequate access to psychotropic drugs.